2015
DOI: 10.3758/s13414-015-1002-6
|View full text |Cite
|
Sign up to set email alerts
|

Spatial priming in ecologically relevant reference frames

Abstract: In recent years, researchers have observed many phenomena demonstrating how the visual system exploits spatial regularities in the environment in order to benefit behavior. In this paper, we question whether spatial priming can be considered one such phenomenon. Spatial priming is defined as a response time facilitation to a visual search target when its spatial position has been repeated in recent trials ( M a l j k o v i c & N a k a y a m a , 1 9 9 6 , P e rc e p t i o n & Psychophysics, 58, 977-991). Does t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 104 publications
1
9
0
Order By: Relevance
“…These results suggest that in the previewed pop-out array, features were processed across the visual field and (1) the singleton attracted attention to its location, (2) this location was remapped across the saccade to maintain the same position in space, and (3) there was no residual benefit at the retinal location. The absence of a residual retinotopic benefit is in line with studies on spatial priming of pop-out (Tower-Richardi et al, 2016). Furthermore, studies that reported a retinotopic advantage across the saccade examined spatial attention for locations defined and known in advance (e.g., , which was not the case here.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…These results suggest that in the previewed pop-out array, features were processed across the visual field and (1) the singleton attracted attention to its location, (2) this location was remapped across the saccade to maintain the same position in space, and (3) there was no residual benefit at the retinal location. The absence of a residual retinotopic benefit is in line with studies on spatial priming of pop-out (Tower-Richardi et al, 2016). Furthermore, studies that reported a retinotopic advantage across the saccade examined spatial attention for locations defined and known in advance (e.g., , which was not the case here.…”
Section: Discussionsupporting
confidence: 85%
“…Furthermore, other studies have examined the reference frame of spatial priming of pop-out (i.e., when repeating the target location in the next search trial improves search performance). In this case, a robust facilitation in the spatiotopic reference frame, and a weaker facilitation in the retinotopic reference frame have been found (Gokce, Müller, & Geyer, 2015;Tower-Richardi, Leber, & Golomb, 2016). In our postsaccadic search task, if the positioning of spatial attention is facilitated by the previewed singleton and its position is remapped across the saccade (e.g., Rolfs et al, 2011), we should find better preview benefits on reaction times when the target remains at the same spatiotopic location.…”
Section: Introductionmentioning
confidence: 56%
See 1 more Smart Citation
“…Thus, while the Spatial Congruency Bias seems to be primarily associated with the type of object-position binding that is not updated with motion, it remains unknown whether this non-updated, retinotopic Congruency Bias reflects a variation of the configural coding mechanism associated with visual working memory (Hollingworth & Rasmussen, 2010), or if it reflects a different, third type of binding mechanism. Future research would be needed to test the Spatial Congruency Bias in the presence of multiple-object arrays, scenes, and/or simultaneous dissociation of retinotopic, spatiotopic, and array-centered reference frames (e.g., Tower-Richardi, Leber, & Golomb, 2016). It is also possible that the Spatial Congruency Bias operates on a different level of perceptual discrimination than the Object-Specific Preview Benefit; while the Congruency Bias is only apparent for fine perceptual discrimination tasks and is argued to influence similarity at a perceptual level (Golomb et al, 2014; see discussion below), object specific-preview benefits are typically seen for coarser discriminations (e.g., a set of 7 nameable colors in Hollingworth & Rasmussen) and primarily influence the speed or accuracy of responses.…”
Section: Discussionmentioning
confidence: 99%
“…To help support all three of these assertions, we briefly review the pertinent subfields of spatial priming along paradigmatic lines to highlight the circumstances that are favorable for a role of response selection in spatial priming. This will lead to the discrimination response hypothesis, which we will test with an ideal data set from an existing study in the intertrial-priming literature on visual search (Tower-Richardi, Leber, & Golomb, 2016). To appreciate the importance of this test, one must keep in mind that this literature has historically favored attentional explanations of spatial priming and has routinely ignored whether response repetition matters.…”
mentioning
confidence: 99%